(untitled) (Web of Teachers: Inderscience Research, 2025)
This article analyzes the strategy of reforms aimed at the formation and development of a digital society in New Uzbekistan. It covers the implementation processes of the digital economy, e-government, and information and communication technologies, as well as their impact on social life, governance systems, and education. Furthermore, the article examines projects carried out under the “Digital Uzbekistan – 2030” strategy, their effectiveness, and state initiatives to enhance the digital competence of the population. The practical significance of this study lies in providing proposals and recommendations to ensure the success of digital transformation processes. The results highlight critical aspects of building a digital society in New Uzbekistan and outline prospective directions for further digital reforms.